Sinonasal papilloma: diagnosis following dental pain. (25th August 2020) - Gallacher, N.; Gormley, M.; Pring, M.; Revington, P.
Abstract: Sinonasal papillomas (SPs) are benign neoplasms that arise within the nasal cavity. Diagnosis may be challenging, given the often non‐specific symptoms including nasal obstruction, headaches and rhinorrhoea. SPs can be locally destructive, have a high tendency to reoccur and may be associated with transformation to squamous cell carcinoma. Management, therefore often, involves surgical excision and careful follow‐up.